The Anthropocene crisis and higher education: A fundamental shift - Carstens, D. (South African Journal of Higher Education, 2016)
This paper seeks to address a fundamental shift that has occurred in reality; a displacement that requires us to critically account for the ways in which knowledge is both being produced and taught at universities. The recent re-naming of the current geological epoch after anthropos has some chilling implications for humans and the ecosystems on which their livelihoods depend. As pedagogues, the crisis of the Anthropocene demands that we make drastic interventions in the way we teach and in what we teach. My aim is to suggest ways in which Deleuzoguattarian schizoanalysis, intersecting as it does with critical posthumanism, the affective turn and the new materialisms, might assist us in this process of crafting socially and environmentally-just pedagogies that are relevant to the contemporary situation. In so doing, I will address some of the uncanny ethical, ontological, epistemological and affective confirgurations of these theoretical perspectives to show how these ideas may impact the curriculum of socially/environmentally just pedagogies and the practice of such pedagogies in higher education.